Increased glutamate levels observed upon functional activation in the anterior cingulate cortex using the Stroop Task and functional spectroscopy. Issue 3 (11th February 2015) - Taylor, Reggie; Schaefer, Betsy; Densmore, Maria; Neufeld, Richard W.J.; Rajakumar, Nagalingam; Williamson, Peter C.; Théberge, Jean
Abstract : It has been shown in recent studies that it is possible to detect changes in the main excitatory neurotransmitter, glutamate, upon functional activation with visual and motor paradigms using a 7 T MRI and functional magnetic resonance spectroscopy. A cognitive task would be desirable for this technique because it could then be used to examine psychiatric disorders that have cognitive deficiencies. The aim of the work presented here was to use functional magnetic resonance spectroscopy with a 7 T MRI to show that increases in glutamate can be observed within the anterior cingulate cortex using the Stroop Task as the activation paradigm in healthy controls. Significant glutamate increases (0.24±0.09 µmol/g, P <0.025), comparable with what has been reported in the studies of the occipital cortex and motor cortex, were observed when the participants ( n =7) performed the task, followed by a trend toward returning to baseline in the post-task recovery period (−0.23±0.13 µmol/g). This method would be ideal for the study of neuropsychiatric disorders that have been shown to have abnormal resting glutamate levels and cognitive deficiencies in the anterior cingulate cortex, such as schizophrenia. This exploratory study is the first to demonstrate functional magnetic resonance spectroscopy in the anterior cingulate with a cognitive task using a 7 T MRI.